Caractérisation Des Boues De Sucrerie Et Des Argiles Pour La Neutralisation Des Résidus Miniers Acides De La Mine De Kettara (Jebilet Centrales, Maroc) - Zerhouni, Youssef; Alikouss, Saida; Saber, Najib; Nfissi, Samiha; Zahour, Ghalem; Baroudi, Zouhir; Samir, Mohamed (European Scientific Journal, ESJ, 2016)
The minerals in the tailings, subject to the action of water and atmospheric oxygen, can generate Acid Mine Drainage (AMD). The latter is considered the most important environmental issue facing the mining industry. Its environmental impacts include the destruction of the flora and fauna in infected rivers and contamination of groundwater. The abandoned mine site Kettara, located about 32 km northwest of Marrakech (Morocco), chosen as a pilot site for this study, more than 3 million tons of tailings stored at ground level without any concern for their environmental consequences. These solid residues, with high concentrations of heavy metals (As, Pb, Fe, Cu ...), produce leachate very acidic (pH <2.9) may contaminate the water resources of the region. To mitigate the DMA phenomenon in this mining site, different protocols have been proposed using candy sludge (Mud Pulp Sweets: MPS), rich in carbonates from the Moroccan Sugar Company Unit (COSUMAR) and red clays (Clays: CLY) of the city of Safi. Physicochemical characterization and mineralogical of these two materials was performed an provided promising results regarding the effectiveness of the use of alkaline materials in the stabilization of tailings Kettara. Indeed, these starting materials are provided with a net neutralizing power which is of the order of 878.5 kg CaCO3 / t for MPS and 299 kg CaCO3 / t for CLY. The valuation of MPS and CLY, as a main component of an alkaline amendment, is likely to significantly reduce the effects of DMA in this semiarid climate mine.